Rhizophoraceae alkaloids : an approach to the synthesis of cassipourine - Morgan, David Lewis (Department of Chemistry, 2016)
The chemistry and structure of cassipourine are outlined, and a number of various possible synthetic approaches are discussed in the light of the chemistry of 1,2-dithiols and of the pyrrolizidine ring system. A route commencing with L-proline having been chosen, this was converted into l-(p-toluenesulphonyl)-pyrrolizidine-2-aldehyde by protecting the amine with the p-toluenesulphonyl group, esterifying, reducing to the alcohol and then oxidising to the aldehyde. The reduction of the corresponding acid chloride direcl1y to the aldehyde proved less successful. The next step envisaged being the preparation of cis-l-[l'-(p-toluenesulphonyl)-pyrrolidin-2'-yl]-1,2-epoxy-3-benzyloxypropane, a number of routes leading to this compound were attempted. The yield of l-[l'-(p-toluenesulphonyl)-pyrrolidin- 2'-yl]-3-benzyloxy-prop-l-ene, prepared by a Wittig reaction was too low for practical purposes. A novel reaction, the fissioning of the sulphonamide bond by the ylid to give 2- benzyloxyethyl-p-tolylsulphone was noted in this preparation. Attempts to prepare trans-l-[l'-(p-toluenesulphonyl)-pyrrolidin- 2'-yl]-3-benzyloxy-prop-l-ene by reduction of ethyl-3-[1'-(p-toluenesulphonyl)- pyrrolidin-2'-yl]-propenoate followed by benzylation were unsuccessful, as were attempts to prepare the same compound by the allylic rearrangement of l-[l'-(p-toluenesulphonyl)- pyrrolidin-2'-yl]-l-hydroxyprop-2-ene. The cis-epoxide was finally successfully prepared by converting the 1-(p-toluenesulphonyl)-pyrrolidine-2-aldehyde into 3-[l'-(p-toluenesulphonyl)-pyrrolidin-2'-yl]-propenoic acid by a Knoevenagel-Doebner reaction. Brominat1on of the double bond was followed by reduction of the acid to an alcohol, which on treatment with base gave a bromo-epoxide. This was treated with benzyl alcohol to form a benzyloxy-brom-hydrin which gave the required cis-l-[l'-(p-toluenesulphonyl)-pyrrolidin-2'-yl]-1,2-epoxy-3-benzyloxypropane. This sequence of reactions was studied first in a series of model compounds, as were the proposed later stages of the synthesis.